Line Balancing Analysis with Ranked Positional Weight (RPW) and Region Approach (RA) Methods on the Production Line at PT. Vitapharm Surabaya - Sugianto, Moch. Febri; Rusindiyanto, Rusindiyanto (SAINTIS Publishing, 2025)
Increasingly fierce industrial competition requires companies to improve the efficiency and productivity of their production processes. PT Vitapharm Surabaya faces the problem of workload imbalance in the Manual-A production line, especially in the facial serum packaging process which has an impact on low production efficiency and non-achievement of daily output targets. This study aims to analyze and improve line balancing using two approaches, namely the Ranked Positional Weight (RPW) and Region Approach (RA) methods. The data collected includes work cycle time, adjustment factors, and allowances for each work element. After the application of RPW and RA methods, there was an increase in line efficiency from 61.10% (actual condition) to 80.56% (RPW) and 84.72% (RA), a decrease in balance delay from 38.90% to 19.44% (RPW) and 15.28% (RA), and a significant reduction in idle time. The results showed that both methods were able to improve the balance of the production line, with the Region Approach method providing slightly more optimal results. This research can be used as a basis for continuous improvement in the cosmetics production line of PT Vitapharm.